2011
DOI: 10.1111/j.1365-2362.2011.02584.x
|View full text |Cite
|
Sign up to set email alerts
|

Claims for improved survival from systemic corticosteroids in diverse conditions: an umbrella review

Abstract: Background Systemic corticosteroids have been proposed for numerous indications and there are many claims that corticosteroids can reduce mortality in diverse conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 52 publications
0
6
0
1
Order By: Relevance
“…17 Of course mortality is a hard endpoint and more difficult to manipulate than other endpoints, but even for mortality, selective analysis may achieve inflated effects, as recently shown by corticosteroid trials. 64 The presence of patterns showing small study effects is also suggestive (not conclusive) of selective reporting biases. 65 Small study effects may also influence the literature in nations with strong traditions of running clinical trials.…”
Section: Possible Explanationsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Of course mortality is a hard endpoint and more difficult to manipulate than other endpoints, but even for mortality, selective analysis may achieve inflated effects, as recently shown by corticosteroid trials. 64 The presence of patterns showing small study effects is also suggestive (not conclusive) of selective reporting biases. 65 Small study effects may also influence the literature in nations with strong traditions of running clinical trials.…”
Section: Possible Explanationsmentioning
confidence: 99%
“…Meta-analysts may have contacted the authors of primary trials and obtained outcome information not reported in published reports, or they may have standardised outcomes, for example, to include all cause mortality and all available follow-up, whereas primary papers may have focused on subset analyses or other secondary analyses such as cause specific deaths. 64 Thus bias may be larger in the reports of primary trials than that seen in meta-analysis based data. Secondly, agreement in treatment effects between more developed and less developed countries does not necessarily mean that both estimates are correct; occasionally both may be equally biased.…”
Section: Potential Limitations Of the Studymentioning
confidence: 99%
“…Umbrella reviews can overcome these problems by assessing the level of the evidence provided by systematic reviews and meta-analyses 14 for each risk or protective factor, through strict criteria that probe a standard list of potential biases. These criteria have been extensively validated in various areas of medicine, such as neurology, oncology, nutrition medicine, internal medicine, psychiatry, paediatrics, dermatology and neurosurgery [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] . In the current study, we applied the umbrella review approach to the published evidence on risk or protective factors for psychotic disorders.…”
mentioning
confidence: 99%
“…By concentrating on each condition individually, guideline writers and opinion leaders may be too hasty in reaching a conclusion that the treatment should not be recommendeddborrowing strength by extrapolating across cancer types may reduce the risk of false-negative study results, especially where the result is imprecise, and there are no compelling biological reasons for diseasespecific effects. Conversely, cautions can be raised on adopting an apparently promising intervention with postulated benefits in many disease areas when examination of evidence does not suggest a consistent effectiveness across different indications [18].…”
Section: Improving Estimates Of Effectivenessmentioning
confidence: 99%